2010
DOI: 10.1124/mol.110.063933
|View full text |Cite
|
Sign up to set email alerts
|

EP1 Prostanoid Receptor Coupling to Gi/oUp-Regulates the Expression of Hypoxia-Inducible Factor-1α through Activation of a Phosphoinositide-3 Kinase Signaling Pathway

Abstract: The EP1 prostanoid receptor is one of four subtypes whose cognate physiological ligand is prostaglandin-E2 (PGE 2 ). It is in the family of G-protein-coupled receptors and is known to activate Ca 2ϩ signaling, although relatively little is known about other aspects of E-type prostanoid receptor (EP) 1 receptor signaling. In human embryonic kidney (HEK) cells expressing human EP1 receptors, we now show that PGE 2 stimulation of the EP1 receptor up-regulates the expression of hypoxia-inducible factor-1␣ (HIF-1␣)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(69 citation statements)
references
References 40 publications
3
64
2
Order By: Relevance
“…It has been previously shown that IL-1b activates HIF1a through the NF-kB-COX2 pathway (34,35). We thus examined whether COX2 is required for the IL1b/HIF1a-mediated repression of mir-101 in NSCLC cells.…”
Section: Il-1b Downregulates Mir-101 Via a Cox2-hif1a Pathwaymentioning
confidence: 94%
“…It has been previously shown that IL-1b activates HIF1a through the NF-kB-COX2 pathway (34,35). We thus examined whether COX2 is required for the IL1b/HIF1a-mediated repression of mir-101 in NSCLC cells.…”
Section: Il-1b Downregulates Mir-101 Via a Cox2-hif1a Pathwaymentioning
confidence: 94%
“…Aside from being a transcription factor in the pathway leading to increased COX-2 levels, HIF-1␣ also participates in considerable cross-talk with the COX-2 pathway. For example, under normoxia the COX-2 end product PGE 2 activates its EP1 receptor to increase HIF-1␣ levels in human embryonic kidney cells (18). During hypoxia, HIF-1␣ binds to the Toll-like receptor 4 promoter causing upregulation of Toll-like receptor 4.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented above demonstrate that PGE 2 acts through a G i/o -coupled GPCR to inhibit I Ca in mouse chromaffin cells. Of the four known receptors for PGE 2 , termed EP1 to EP4, only EP3 typically couples to G i/o -type G proteins, although it has been reported that EP1 receptors might also couple to G i/o at least in some cell types (Ji et al, 2010). Both EP3 and EP1 receptors have been reported previously in the adrenal medulla (Breyer et al, 1993;Namba et al, 1993;Engström et al, 2008). ]…”
Section: Short-term Application Of Pgementioning
confidence: 99%